Mindful gratitude journaling: psychological distress, quality of life and suffering in advanced cancer: a randomised controlled trial - Tan, Ting Ting; Tan, Maw Pin; Lam, Chee Loong; Loh, Ee Chin; David Paul, Capelle; Sheriza Izwa, Zainuddin; Ang, Bin-Ting; Lim, Min Ai; Lai, Natalie Zi; Tung, Yu-Zhen; Yee, Hway Ann; Ng, Chong Guan; et al. (BMJ Publishing Group Ltd., 2021)
Context Numerous studies have shown that gratitude can reduce stress and improve quality of life.